General practitioners in front of COVID-19: Italy in European comparative perspective - Genova, Angela; Lombardini, Simone (Frontiers in Sociology, 2024)
COVID-19 has highlighted strengths and weaknesses in healthcare systems on a global scale. Despite the differences in primary care models in Europe, this study investigates the state of the art of general practitioners (GP) before the COVID-19 pandemic spread as the result of the reform process of the previous two decades. The GP numbers of over 100,000 inhabitants have been considered a proxy of public health investment in GPs. Has the number of GPs increased or decreased in the last twenty years of reform processes in European countries? The primary hypothesis is that European healthcare systems would have coherently increased the number of GPs following the WHO recommendations. Comparative data on the number of GPs per 100,000 inhabitants in 21 European countries is investigated between 1995 and 2014 (the last available data). Data shows that the number of family doctors over 100,000 inhabitants in European countries has increased over the last twenty years, except for Italy, where it has strongly reduced. Primary care has had a crucial role in managing the pandemic. This study’s results suggest that countries like Italy that have not invested in family doctors in the last two decades would have been ill-equipped to handle the COVID-19 pandemic.